Facile synthesis, characterization of various polymer immobilized on magnetite nanoparticles applying the coprecipitation method. Issue 5 (31st August 2021) - Hayashi, Kodai; Tomonaga, Hitoshi; Matsuyama, Tatsushi; Ida, Junichi
Abstract: In this study, systematic examination of the effect of different polymer types (functional groups) on the one‐step synthesis of polymer immobilized magnetite nanoparticle via the modified coprecipitation method was carried out. By using five different polymers with different functional groups of polyacrylic acid (PAA), polyacrylamide (PAM), polyethylene glycol (PEG), polyethylene imine (PEI), and polyvinyl alcohol (PVA), the effect of the polymer difference on magnetite nanoparticle formation, polymer immobilization, composite particle size, zeta potential and magnetic properties of the resulting composite were measured in detail. The results show that the immobilized polymer yield varied significantly depending on the type of polymer used and their order was as follows; PEG < PEI < PAM < PAA < PVA. Despite the simple method, PVA/MNP achieved high immobilized polymer amount of 0.2 g/(g‐Fe3 O4 ), which was about 1.8 times larger than that prepared by a conventional method. Furthermore, the different zeta potentials and hydrodynamic diameter corresponding to each functional group of the immobilized polymer were observed. The results of the vibrating sample magnetometer (VSM) measurement confirmed that all the polymer/MNP composites showed a superparamagnetic behavior. These results showed that the proposed method is very simple, facile, and applicable to various polymers to synthesize polymer immobilized on magnetite nanoparticle. Abstract :